2013
DOI: 10.1080/08927014.2013.847927
|View full text |Cite
|
Sign up to set email alerts
|

Staticvsdynamic settlement and adhesion of diatoms to ship hull coatings

Abstract: Many experiments utilize static immersion tests to evaluate the performance of ship hull coatings. These provide valuable data; however, they do not accurately represent the conditions both the hull and fouling organisms encounter while a ship is underway. This study investigated the effect of static and dynamic immersion on the adhesion and settlement of diatoms to one antifouling coating (BRA 640), four fouling-release coatings (Intersleek(®) 700, Intersleek(®) 900, Hempasil X3, and Dow Corning 3140) and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…The two test sites were chosen since the population density and the seasonal variation of organisms have been studied extensively at both sites (Swain et al 2006;Zargiel et al 2011;Sweat and Johnson 2013;Zargiel and Swain 2013;Ralston and Swain 2014). The water was used to precondition self-assembled monolayers (SAMs) with different end group chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…The two test sites were chosen since the population density and the seasonal variation of organisms have been studied extensively at both sites (Swain et al 2006;Zargiel et al 2011;Sweat and Johnson 2013;Zargiel and Swain 2013;Ralston and Swain 2014). The water was used to precondition self-assembled monolayers (SAMs) with different end group chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to non-specific protein adsorption may be considered to be a general indication of surface inertness, but its use here is also related to potential biomedical applications, as well as a means to explore the relevance of protein adsorption tests as predictors of marine antifouling properties. U. linza is a major macrofouling alga which colonizes surfaces through the production of vast quantities of microscopic motile spores (Callow and Callow 2006), while diatoms are interesting microfoulers in that they frequently succeed in fouling submerged artificial surfaces, and produce thick slime even on biocidal antifouling paints, and also adhere tenaciously to fouling-release coatings based on silicone elastomers (Zargiel et al 2011, Zargiel andSwain 2014). Three oligo(lactose) thiols, forming di-, tetra-and hexasaccharides (containing 1, 2, and 3 lactoside groups, respectively, see Figure 1), were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the development of marine antifouling technology, people initially focused on the diatom community structure of the antifouling coating surface. Zargiel et al (2011) andSwain (2014) reported that the hull coatings of cargo ships affected the community structure of fouling diatoms, and the main fouling diatom species varied signifi cantly with different coatings and the geographical area. The effects of static and dynamic immersion on the adhesion and settlement of diatoms were different, and the diversity of diatoms on static panels was signifi cantly greater than that on dynamic panels.…”
Section: Introductionmentioning
confidence: 99%